Impulse purchasing during Covid-19: a quantitative study in Kuala Lumpur - Venkatesh, Madhan (2022)
COVID-19 and the subsequent lockdown has had a tremendous impact on consumer behavior of people. This paper seeks to evaluate how COVID-19 has affected consumer behavior.